2019
DOI: 10.1016/j.jhealeco.2019.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Competition and physician behaviour: Does the competitive environment affect the propensity to issue sickness certificates?

Abstract: runs a publication series consisting of two parts, Reports and Working Papers. The Director of the Uni Research Rokkan Centre together with the Research Directors form the editorial board of the publication series. The Report series includes scientific papers, such as final reports on research projects. The manuscripts are accepted by the editorial board, normally after a peer review. The Working Paper series includes working papers, lecture transcripts and seminar papers. The manuscripts published as Working … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…2 Roth et al (1991) observe that increased competition leads to fewer 'fair' outcomes in the lab. Cai & Liu (2009) report that firms in more competitive markets engage in more tax avoidance activities in China; Brekke et al (2017) and Markussen & Røed (2017) discover that general practitioners in Norway are more lenient gatekeepers, the more competitive the market for their services is; Lee et al (2018) observe less CSR activity in the more competitive markets in South Korea. While Falk & Szech (2013) and Bartling et al (2015) observe that intrinsic CSR behavior may be eroded in market settings, they find no significant effects on CSR activities from varying the number of competing subjects.…”
Section: Introductionmentioning
confidence: 99%
“…2 Roth et al (1991) observe that increased competition leads to fewer 'fair' outcomes in the lab. Cai & Liu (2009) report that firms in more competitive markets engage in more tax avoidance activities in China; Brekke et al (2017) and Markussen & Røed (2017) discover that general practitioners in Norway are more lenient gatekeepers, the more competitive the market for their services is; Lee et al (2018) observe less CSR activity in the more competitive markets in South Korea. While Falk & Szech (2013) and Bartling et al (2015) observe that intrinsic CSR behavior may be eroded in market settings, they find no significant effects on CSR activities from varying the number of competing subjects.…”
Section: Introductionmentioning
confidence: 99%
“…However, jurisdictions that have changed the reimbursement rate, introducing economic incentives have succeeded [ 19 ]. Several recent studies using Norwegian data conclude that sickness absence is indeed possible to influence by moderate institutional changes, whether it is closer follow-up by NAV and change of wording in the communication to the sick-listed [ 20 ], the regular GP’s use of graded sick leave [ 21 , 22 ], degree of GP competition [ 5 , 6 ] or GP remuneration schemes [ 23 ]. Thus, the incentives that GPs and sick listed are faced with seem to matter.…”
Section: Discussionmentioning
confidence: 99%
“…Although Norwegian GPs are constantly urged by the authorities to motivate and focus on RTW possibilities, the effort put into this task probably varies considerably. Patients have the option to change GP twice a year and studies have shown that competition for patients affect the GP’s sick listing behaviour [ 5 , 6 ]. In Norway, graded sick leave is a priority tool in efforts to reduce sick leave [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…For (local) physician markets, field evidence is scarce and rather mixed, however (Gaynor & Vogt, 2003). On the one side, empirical studies indicate that competition in primary care appears to have a positive impact on for example, patient satisfaction (Dietrichson et al., 2020; Gravelle et al., 2019), the number of diagnoses (Dackehag & Ellegård, 2019), the number of referrals (Godager et al., 2015; Iversen & Ma, 2011), the type of health care services provided (Dunn & Shapiro, 2018), the number of health outcomes (Koch et al., 2018), and the number of sick leave certificates (Brekke et al., 2019). On the other side, there are field studies finding no or negative effects on quality indicators, like the length of consultation (Gravelle et al., 2016; Johar et al., 2014).…”
Section: Related Literaturementioning
confidence: 99%